2018
DOI: 10.1063/1.5016814
|View full text |Cite
|
Sign up to set email alerts
|

Microphase separation and the formation of ion conductivity channels in poly(ionic liquid)s: A coarse-grained molecular dynamics study

Abstract: We study generic properties of poly(ionic liquid)s (PILs) via coarse-grained molecular dynamics simulations in bulk solution and under confinement. The influence of different side chain lengths on the spatial properties of the PIL systems and on the ionic transport mechanism is investigated in detail. Our results reveal the formation of apolar and polar nanodomains with increasing side chain length in good agreement with previous results for molecular ionic liquids. The ion transport numbers are unaffected by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 72 publications
1
25
0
Order By: Relevance
“…is also of fundamental importance for LIBs or LMBs, as it mainly determines the charging and discharging rates. For highly effective electrolyte solutions or single ion conductors, one can observe values of t + > 0.5 [9,97], whereas most values in organic liquid electrolyte solutions are t + < 0.5 [6,9]. The corresponding value reveals that anions instead of cations mostly contribute to the ionic conductivity as an unwanted side effect in organic solvent-based LIBs.…”
Section: Ion Correlation Effects and Transport Behaviormentioning
confidence: 97%
See 1 more Smart Citation
“…is also of fundamental importance for LIBs or LMBs, as it mainly determines the charging and discharging rates. For highly effective electrolyte solutions or single ion conductors, one can observe values of t + > 0.5 [9,97], whereas most values in organic liquid electrolyte solutions are t + < 0.5 [6,9]. The corresponding value reveals that anions instead of cations mostly contribute to the ionic conductivity as an unwanted side effect in organic solvent-based LIBs.…”
Section: Ion Correlation Effects and Transport Behaviormentioning
confidence: 97%
“…With regard to the influence of ion correlations on charge transport, the ideal ionic conductivity for non-interacting, i.e., ideal, ions is given by the Nernst-Einstein equation, which for a 1:1 salt in the limit of long times reads [96,97]…”
Section: Ion Correlation Effects and Transport Behaviormentioning
confidence: 99%
“…Furthermore and in close agreement with the previously discussed dielectric decrement effects, the presence of uncharged co-solvent molecules also induces global variations of the dielectric constant. For a mole fraction of the co-solvent species x cs in a binary solution, the ideal dielectric constant of a homogeneous solution reads sol r = s r (1 − x s ) + cs r x s (28) which shows a linear variation between the individual dielectric constants s r and cs r of the pure solvent or co-solvent solution, respectively. Hence, with increasing mole fraction of the co-solvent, one usually observes a change of the dielectric constant from the value for the pure solvent towards the dielectric constant of the pure co-solvent.…”
Section: Co-solute and Co-solvent Effectsmentioning
confidence: 99%
“…For instance, previous atomistic MD simulations revealed that the molecular solvation behavior influences significantly the amount of dissociated counterions, and thus the corresponding conformational behavior with regard to repulsive electrostatic interactions or charge screening effects along the polyelectrolyte backbone [18,24,25]. The molecular arrangement of the solvent molecules is influenced by the presence of the polyelectrolyte as manifested by local variations of the dielectric constant, charge hydration asymmetry effects or modified charge transport mechanisms [26][27][28]. Comparable molecular interactions also dominate the occurrence of various polyelectrolyte structures in bulk phase, as can be seen by the formation of polyelectrolyte micelles, pearl-necklace structures, the onset of microphase separation processes between polar and apolar regions as well as the formation of polyelectrolyte complexes [29][30][31][32][33][34] and coacervates [35].…”
Section: Introductionmentioning
confidence: 99%
“…Previous atomistic MD simulations, for example, showed that the behavior of molecular solving greatly influences the sum of dissociated counterions and hence the resulting conformational behaviour of repulsive electrostatic interactions or charge screening effects along the polyelectrolyte backbone [9,14,15]. The presence of the polyelectrolyte as expressed by local dielectric constant changes, asymmetry effects of charge hydration, or modified charge transfer mechanisms [16][17][18], affects the molecular structure of the solvent molecules. The chemical structure of glutamic acid (Fig.…”
Section: Introductionmentioning
confidence: 99%